Climate-smart agriculture is good for business: A framework for establishing the business case for climate-smart agriculture investments - Nowak, Andreea C.; Steward, Peter R.; Namoi, Nictor; Mayzelle, Megan; Kamau, Hannah N.; Lamanna, Christine; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate-smart agriculture (CSA) makes financial sense for businesses. Governments are increasingly holding the private sector responsible for their role in climate change impacts. Extreme weather events are incredibly costly for businesses. This is particularly true in agriculture, which relies heavily on favorable weather conditions. CSA practices and technologies are central to the transformative changes necessary to maintain the stability—and profitability—of the food system in the face of climate change. Where robust information on the benefits, costs, and risks of interventions is missing or incomplete, would-be investors, including donors, governments, businesses, and farmers, remain uninformed of the potentially massive dividends climate-smart investments could offer. This dearth of viable business models ultimately hinders the mainstreaming of productive, climate-resilient, low-emissions agriculture. Robust business-case analyses of CSA could accelerate the scaling of promising, profitable technologies by transparently and rigorously laying out the monetary and nonmonetary values of performance. We use existing data from Evidence for Resilient Agriculture (ERA, previously known as The Compendium) to develop a general framework for establishing the business case for specific farm-level agricultural technologies. The framework focuses on the costs, benefits, and risks of adoption of CSA by smallholder farmers. We illustrate the application of the framework with two case studies in Kenya and Malawi to highlight opportunities, challenges, and lessons learned from building business cases for CSA. These give potential investors the tools to screen and select appropriate technologies and help de-risk investments where data are few and far between.